Fungal Infections: Epidemiology, Clinical Challenges, and Advances in Diagnosis and Treatment - a review - Klimas, Filip; Zatłoka-Mazur, Dorota; Rusiński, Kacper; Zając, Piotr; Pawłowski, Bartosz; Sienkiewicz, Michał; Potoczek, Adriana; Zięba, Zuzanna; Pudełko, Iwona (Quality in Sport, 2025)
Fungal infections are a serious public health threat, affecting a wide variety of populations worldwide. This review presents the current state of knowledge on fungal infections, focusing on epidemiology, etiology, clinical manifestations, and emerging trends. Findings are based on 35 peer-reviewed studies and focus on both well-known and emerging fungal pathogens, diagnostic advances, and therapeutic challenges. In addition, this review emphasizes the role of environmental and social factors in shaping the dynamics of fungal disease and highlights the importance of a global, multidisciplinary effort to combat the rise in fungal disease. The literature for this review was collected from PubMed and Google Scholar using the key words “fungal infections” combined with “epidemiology”, “etiology”, “risk factors”, “symptoms”, “complications”, “treatment”, and “trends”.